2009
DOI: 10.1007/s10447-008-9066-9
|View full text |Cite
|
Sign up to set email alerts
|

Wellness and Self-esteem Among Turkish University Students

Abstract: This study investigated the differences among 465 Turkish first year university students regarding overall wellness and four of its dimensions (cognitive emotional wellness-CEW, relational wellness-RW, life goal-LG, and physical wellness-PW) in terms of self-esteem levels and gender. The data were gathered by administering the Rosenberg Self-Esteem Scale and a short-form of the Wellness Inventory (WI-30). The results of ANOVA showed significant main effects for high-low self-esteem and gender, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…In fact, gender does not mediate the SAO model which is in contrast to the finding from other scholars which found that gender mediated self-esteem (Duran & Tezer, 2009, Karagozoglu et al 2008, Sherina et al 2008, Kundu & Rani, 2007, Aricak, 2007, and McMullin & Cairney, 2004. Another www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Discussioncontrasting
confidence: 60%
“…In fact, gender does not mediate the SAO model which is in contrast to the finding from other scholars which found that gender mediated self-esteem (Duran & Tezer, 2009, Karagozoglu et al 2008, Sherina et al 2008, Kundu & Rani, 2007, Aricak, 2007, and McMullin & Cairney, 2004. Another www.ccsenet.org/ass Asian Social Science Vol.…”
Section: Discussioncontrasting
confidence: 60%
“…Wellness is a multidimensional and multidisciplinary concept. Although definitions may vary depending on the context, generally, wellness is thought to be a balanced state of a healthy body, mind, and spirit [7,9,10,[26][27][28]. Wellness can be seen as a highlevel concept that integrates multiple domains, including the physical, psychological, social, and spiritual domains, and it may vary according to age or cultural context [29].…”
Section: Conceptualizing Personal Wellnessmentioning
confidence: 99%
“…Wellness is thought to be a subjective feeling of health and well-being [9]. Wellness considers individuals' general functioning as a whole, covering not only physical but also social and psychological aspects [9,10]. Wellness is a multidimensional concept, and it is currently being studied in many different scientific areas, such as medicine, public health, occupational health, and mental health [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there exist several wellness definitions and they vary depending on the context. Often wellness is thought to be a balanced state of a healthy body, mind and spirit which creates a harmonious feeling of complete wellness (Myers and Sweeney, 2004;Larson, 1999;Oguz-Duran and Tezer, 2009;Mackey, 2009;Soomlek and Benedicenti, 2010;Kirsten et al, 2010;Kiefer, 2008). Most wellness models support health promotion, prevention, and progress towards better functioning (Larson, 1999;Conrad, 1994;Sterling et al, 2010).…”
Section: Literature and Contextual Analysesmentioning
confidence: 99%
“…Thus, wellness is seen as a high level concept integrating multiple domains (Schuster et al, 2004;Sterling et al, 2010;Kirsten et al, 2010;Kiefer, 2008). The concept wellness contains individuals' functioning as a whole and it acknowledges lifestyle, behavior, culture, beliefs, experiences and other issues affecting general life satisfaction (Oguz-Duran and Tezer, 2009;Mackey, 2009;Soomlek and Benedicenti, 2010;Sterling et al, 2010;Kiefer, 2008;Ahtinen et al, 2008).…”
Section: Literature and Contextual Analysesmentioning
confidence: 99%